2015
DOI: 10.1111/pan.12593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a neck collar on upper airway size in children sedated with propofol–midazolam combination during magnetic resonance imaging

Abstract: Application of a soft neck collar in children aged 2-4 years may enhance the retropalatal and retroglossal airway dimensions during pediatric sedation in the supine position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…This unusually high incidence of upper airway obstruction may have been due to our use of relatively low infusion rates of propofol. While considerably higher propofol infusion rates up to 250 mcg·kg −1 ·min −1 have been successfully used for MRI , the lower doses of propofol used in our study are consistent with infusion rates reported in the literature , particularly when accompanied by premedication . Indeed prior to using the new 3T MRI, our standard propofol sedation regimen for the 1.5T MRI, preceded by midazolam premedication, had been highly successful.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This unusually high incidence of upper airway obstruction may have been due to our use of relatively low infusion rates of propofol. While considerably higher propofol infusion rates up to 250 mcg·kg −1 ·min −1 have been successfully used for MRI , the lower doses of propofol used in our study are consistent with infusion rates reported in the literature , particularly when accompanied by premedication . Indeed prior to using the new 3T MRI, our standard propofol sedation regimen for the 1.5T MRI, preceded by midazolam premedication, had been highly successful.…”
Section: Discussionsupporting
confidence: 85%
“…The loading doses of dexmedetomidine and induction doses and maintenance infusion rates for propofol used in this study have been reported as safe and effective dosing regimens in the literature for MRI . Continuous infusion rates for propofol were lower than a number of reported studies yet similar to studies where premedication was used prior to procedural sedation . We used a modified (in reverse order) Children's Hospital of Wisconsin Sedation Scale to assess sedation levels (0 Inadequate: anxious, agitated, or in pain; 1 Minimal: spontaneously awake without stimulus; 2 Drowsy: eyes open or closed, but easily arouses to consciousness with verbal stimulus; 3 Moderate‐deep: arouses to consciousness with moderate tactile or loud verbal stimulus; 4 Deep: arouses slowly to consciousness with sustained painful stimulus; 5 Deeper: arouses, but not to consciousness, with painful stimulus; 6 Anesthesia: unresponsive to painful stimulus) .…”
Section: Methodsmentioning
confidence: 97%
“…Vialet, Nau, Chaumoître, and Martin demonstrated that slight extension of the head in infants and young children considerably improved the alignment of the axes of the airway [22]. Another MRI study showed that application of a soft neck collar in children aged 2 -4 years may expand the retropalatal and retroglossal airway dimension during sedation in the supine position [23]. The underlying mechanism may be the slight extension of the head with anterior protrusion of the mandible achieved by the neck collar.…”
Section: Head and Neck Positionmentioning
confidence: 99%
“…The underlying mechanism may be the slight extension of the head with anterior protrusion of the mandible achieved by the neck collar. Mustafa, Emara, and Nouh suggested that displacing the mandible pulls the tongue forward and subsequently increases the caliber of the retroglossal airway [23]. In addition, the retropalatal airway improves as the soft palate is displaced for-ward because it is coupled to the tongue through the fauces [24].…”
Section: Head and Neck Positionmentioning
confidence: 99%
“… 4 Recently, the impact of Neck Collars (NC), which prevent downward dislocation of the mandibula, was shown to improve the airway patency in children undergoing MRI examination. 5 However, in that study, only children aged between 2 and 4 years were investigated.…”
Section: Introductionmentioning
confidence: 99%